Human Resource Planning, Opportunities and Manpower in Increasing Economic Growth (Case Study of Industrial Revolution 4.0) - Irma Hetty Siregar; Khaidar Ibrahim; Lidya Laras Murdiantoro Pratama; Hadi Supratikta (Indonesian Development of Economics and Administration Journal, 2023)
This research is a literature study, which is carried out through journal reviews and literature studies relevant to the research. The type of data used is secondary data, that is, data obtained indirectly. Data collection techniques are carried out by reviewing and analyzing books and journals with rules related to compensation planning. From the results of this study, it is known that compensation planning is very important.Human resource planning is the process of analysis and identification carried out by the organization on the needs of human resources, so that the organization can determine the steps to be taken to achieve its goals. The industrial revolution 4.0 will bring many changes with all the consequences. The industry will be more compact and efficient. But there are also risks that may arise. For example, reduced human resources that will be replaced by machines or robots. There will be more opportunities if it is in accordance with existing capabilities, as well as a qualified workforce that can keep up with the changing times in the current era. This study aims to determine Human Resources in increasing economic growth. Where, Human Resources are required to see opportunities, face challenges and be competent in increasing growth.